Seed Germination Ecophysiology of Acacia dealbata Link and Acacia mearnsii De Wild.: Two Invasive Species in the Mediterranean Basin - Dessì, Ludovica (2021)
Acacia dealbata and A. mearnsii are two invasive species found in coastal, mountain, and riparian Mediterranean habitats. Seed biology and germination traits are important drivers of the competitive performance of plants and may significantly contribute to biological invasions. The seeds of Acacia s.l. have physical dormancy due to an impermeable epidermal layer. The aim of this study was to assess the germination capacity of scarified and non-scarified seeds of A. dealbata and A. mearnsii from different areas of the Mediterranean Basin. To test the seed imbibition capacity, the increase in mass was evaluated. Non-scarified seeds were tested at 15, 20, and 25 C in light conditions. Scarified seeds were tested at 5, 10, 15, 20, and 25 C and 25/10 C in light and dark conditions. Scarified seeds increased in mass more than non-scarified seeds. Both species showed a higher germination capacity at 25 C in non-scarified seeds; A. dealbata reached a germination maximum of 55%, while A. mearnsii reached 40%, showing a difference among these populations. Scarified seeds of both species reached germination percentages >95% at all temperatures except at 5 C in dark conditions. Scarification was necessary to break dormancy and promote germination. The present study provides new knowledge about the seed ecology and germinative behaviour of the two Acacia species under different pre-treatment, temperature, and photoperiod regimes, contributing to the understanding of their invasive behaviour.